2015
DOI: 10.1056/nejmoa1510188
|View full text |Cite|
|
Sign up to set email alerts
|

Paclitaxel-Eluting versus Everolimus-Eluting Coronary Stents in Diabetes

Abstract: In patients with diabetes mellitus and coronary artery disease undergoing PCI, paclitaxel-eluting stents were not shown to be noninferior to everolimus-eluting stents, and they resulted in higher rates of target-vessel failure, myocardial infarction, stent thrombosis, and target-vessel revascularization at 1 year. (Funded by Boston Scientific; TUXEDO-India Clinical Trials Registry-India number, CTRI/2011/06/001830).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(55 citation statements)
references
References 16 publications
4
47
2
2
Order By: Relevance
“…Furthermore, these trials compared CABG against PCI with bare metal stents and first-generation drug-eluting stent (paclitaxel or sirolimus-eluting stents), and findings from recent studies suggest that the superiority of CABG over PCI may be less clear with the use of newer generation drug-eluting stent. [22][23][24] The results from our present analysis provide an insight into the contemporary patterns of revascularization among patients with DM and multivessel CAD in the setting of NSTEMI. We observed greater utilization of PCI versus CABG in this patient population throughout the study period.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, these trials compared CABG against PCI with bare metal stents and first-generation drug-eluting stent (paclitaxel or sirolimus-eluting stents), and findings from recent studies suggest that the superiority of CABG over PCI may be less clear with the use of newer generation drug-eluting stent. [22][23][24] The results from our present analysis provide an insight into the contemporary patterns of revascularization among patients with DM and multivessel CAD in the setting of NSTEMI. We observed greater utilization of PCI versus CABG in this patient population throughout the study period.…”
Section: Discussionmentioning
confidence: 84%
“…Along this line, a recent randomised trial comparing PCI with EES against CABG for the treatment of left main disease reported similar outcomes for both revascularisation techniques at 3-year follow-up, with very low rates of stent thrombosis (0.7%) 39. The superiority of limus-based, new-generation DES for parameters of both efficacy and safety has been also established in patients with diabetes, for whom a benefit of PES was initially postulated 40. Moreover, new-generation DES represent the most effective therapy for the treatment of in-stent restenosis with a difference in diameter stenosis of about 10% at angiographic follow-up when compared against drug-coated balloons 41.…”
Section: Introductionmentioning
confidence: 92%
“…Одна из последних публикаций посвящена сравнению результатов имплан-тации стентов PES и EES у больных с СД (TUXEDO trial, 2015). При использовании PES у больных СД в течение года наблюдения отмечены существенно и достоверно более высокая частота развития спонтанных ИМ, тром-боза стента, повторных таргетных реваскуляризаций, причем результаты не зависели от того, получает ли па-циент инсулин [21].…”
Section: сахарный диабет Diabetes Mellitusunclassified